How Residents Develop Trust in Interns: A Multi-Institutional Mixed-Methods Study. (October 2016) - Sheu, Leslie; O'Sullivan, Patricia S.; Aagaard, Eva M.; Tad-y, Darlene; Harrell, Heather E.; Kogan, Jennifer R.; Nixon, James; Hollander, Harry; Hauer, Karen E.
Abstract : Purpose: Although residents trust interns to provide patient care, little is known about how trust forms. Method: Using a multi-institutional mixed-methods study design, the authors interviewed (March–September 2014) internal medicine (IM) residents in their second or third postgraduate year at a single institution to address how they develop trust in interns. Transcript analysis using grounded theory yielded a model for resident trust. Authors tested (January–March 2015) the model with residents from five IM programs using a two-section quantitative survey (38 items; 31 rated 0 = not at all to 100 = very much; 7 rated 0 = strongly disagree to 100 = strongly agree) to identify influences on how residents form trust. Results: Qualitative analysis of 29 interviews yielded 14 themes within five previously identified factors of trust (resident, intern, relationship, task, and context). Of 478 residents, 376 (78.7%) completed the survey. Factor analysis yielded 11 factors that influence trust. Respondents rated interns' characteristics (reliability, competence, and propensity to make errors) highest when indicating importance to trust (respective means 86.3 [standard deviation = 9.7], 76.4 [12.9], and 75.8 [20.0]). They also rated contextual factors highly as influencing trust (access to an electronic medical record, duty hours, and patient characteristics; respective means 79.8 [15.3], 73.1 [14.4], and 71.9 [20.0]). Conclusions: Residents form trust based on primarily intern- and context-specific factors. Residents appear to consider trust in a way that prioritizes interns' execution of essential patient care tasks safely within the complexities and constraints of the hospital environment. Abstract : Supplemental Digital Content is available in the text.